Pendidikan Kesehatan dan Pendampingan Pembuatan Makanan Pendamping Air Susu Ibu pada Ibu Balita di Desa Sukasukur, Kecamatan Cisayong, Kabupaten Tasikmalaya - Rismawati, Sariestya; Putri, Dinda Hermalia (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
The health and nutritional status of children is one of the issues and problems faced in Indonesia, one of which is malnutrition. Data shows that the incidence of malnutrition in children aged 6-23 months in Indonesia reaches 11.4% for undernutrition, 30% for stunting and 11.7% for wasting. This nutritional problem is related to food intake that is not in accordance with the nutritional needs of children, including the provision of complementary food for ASI which is of poor quality and not optimal. The aim of this study was to increased the knowledge and skills in making complementary foods for ASI. The community service method used in this study is in the form of health education and assistance in the practice of making MPASI. The result showed that there was an increase in knowledge and skills in making complementary foods for ASI. Suggestions for the future are that mothers can empower themselves by increasing knowledge about patterns of supplementary feeding for children from various sources.